Efektivitas Penggunaan Media Sosial Pada Pembelajaran Pendidikan Agama Islam (PAI) Siswa Kelas XI di SMK N 1 Wonosobo - Fahmi Hidayat; Noor Aziz; Nugroho Prasetya Adi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to: 1) Find out how social media is used in PAI learning for class XI DKV 1 SMK N 1 Wonosobo students. 2) Find out to what extent the use of social media is effective in learning PAI for class XI DKV 1 SMK 1 Wonosobo students. 3) Knowing the advantages and disadvantages of using social media in learning Islamic Religious Education for class XI DKV 1 students at SMK N 1 Wonosobo.This thesis uses a qualitative research approach, where the type of research is descriptive, namely research that seeks to observe problems systematically and accurately regarding the facts and characteristics of certain objects. Descriptive research aims to explain, describe and map facts based on a certain perspective or frame of mind. The results of the research show that the use of social media in PAI learning for class The advantages of using social media in learning consist of: 1) Wide access to information, 2) Interaction and discussions in class become more interesting, 3) Learning is more collaborative, 4) Flexibility in time and place. On the other hand, advantages definitely have disadvantages in the learning process using social media, including: 1) Uncontrolled content, 2) Disruption and Ablation, 3) Limited control and supervision, 4) Dependence on technology.